2011
DOI: 10.4187/respcare.01011
|View full text |Cite
|
Sign up to set email alerts
|

Higher PEEP in Patients With Acute Lung Injury: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: Studies of ventilation strategies that included higher PEEP in patients with acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) have yielded conflicting results. OBJECTIVE: To determine whether higher PEEP during volume-limited and pressure-limited ventilation is associated with 28-day mortality or barotrauma rates in patients with ALI/ARDS. METHODS: We searched MEDLINE, CENTRAL, EMBASE, CINAHL, Web of Science, and the bibliographies of retrieved papers to identify randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 50 publications
1
22
0
3
Order By: Relevance
“…Currently, lung-protective pressureand volume-limited ventilatory strategies aimed at mitigating ventilator-associated lung injury have become the standard of care (2). Clinical trials evaluating the use of higher positive end-expiratory pressure, recruitment maneuvers, high-frequency oscillatory ventilation, and prone positioning to further optimize lung protection in patients with ARDS have yielded variable results (4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Currently, lung-protective pressureand volume-limited ventilatory strategies aimed at mitigating ventilator-associated lung injury have become the standard of care (2). Clinical trials evaluating the use of higher positive end-expiratory pressure, recruitment maneuvers, high-frequency oscillatory ventilation, and prone positioning to further optimize lung protection in patients with ARDS have yielded variable results (4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Several study-level 45,46 and individual patient data meta-analyses 47 have further evaluated the association between higher PEEP strategies and mortality. Although all included ALVEOLI, ExPress, and LOV, 1 meta-analysis 45 included a fourth study that used esophageal pressure measurements to ensure a positive end-expiratory transpulmonary pressure in the experimental group.…”
Section: Targeting Atelectrauma and Lung Recruitment -Higher Versus Lmentioning
confidence: 99%
“…To help answer this question a studylevel meta-analysis of 4 randomized trials was reported in 2011. 69 Four previous meta-analyses have assessed similar questions. 70 -73 Like these prior meta-analyses, this study included the same 3 large multicenter randomized controlled trials, 58,74,75 but this is the first meta-analysis to include the recent single-center study using esophageal manometry to set PEEP.…”
Section: Acute Lung Injury and Acute Respiratory Distress Syndromementioning
confidence: 99%